Factors Associated With the Efficacy of Probing for Adult Patients With Lacrimal Duct Obstruction. Issue 2 (March 2017) - Ohtomo, Kazuyoshi; Ueta, Takashi
Abstract : Purpose: To investigate the factors associated with the effectiveness of probing for epiphora in adults with lacrimal duct obstruction. Methods: This was a cross-sectional retrospective study involving 116 eyes of 82 patients (26 males and 56 females) with a primary acquired lacrimal duct obstruction who received a probing from June 2007 to October 2013. The influences of age, gender, the duration of the symptom before probing, the number of probing treatments during the follow-up period, locations of the obstructions, and the presence of mucopurulent discharge upon irrigation of the lacrimal sac on the efficacy of probing were evaluated. Results: Obstructions were observed in the nasolacrimal duct, common canaliculus, canaliculus, and punctum for 76% (88/116), 22% (26/116), 4% (5/116), and 3% (3/116), respectively. The overall efficacy of probing was 52% (60/116). Between the effective group and the noneffective group, 77% (20/26) of the common canaliculus obstructions were found in the effective group ( p = 0.0039), whereas 67% (29/43) of the cases with discharge from the lacrimal sac were found in the noneffective group ( p = 0.0020). On logistic regression analysis, the efficacy of probing was increased by the presence of common canaliculus obstruction (odds ratio = 6.0408; 95% confidence interval = 1.1255–48.9179, p = 0.0353), but was decreased by the presence of discharge from the lacrimal sac (odds ratio = 0.3508; 95% confidence interval = 0.1425–0.8345, p = 0.0176). Conclusion: Probing can be a therapeutic choice for lacrimal duct obstructions, particularly when there is a common canaliculus obstruction and no discharge from the lacrimal sac. Abstract : A probing procedure can be a therapeutic selectionin a situation of a common canaliculus obstruction without discharge from the lacrimal sac.